Playing not once, not twice but three times in a day: the effect of fatigue on performance in junior tennis players. (2nd January 2018) - Maraga, Nathanial; Duffield, Rob; Gescheit, Danielle; Perri, Thomas; Reid, Machar
Abstract: This study examined physical and perceptual responses to multiple daily tennis matches. Six junior males completed 3 × 90 min singles matches, each separated by 45 min recovery. Physical capacity (agility, countermovement jump [CMJ]), shoulder internal and external rotation (IR, ER), serve performance, creatine kinase (CK) and perceptual (soreness, pain and fatigue) measures were performed before match 1 and following each match. During matches, distances and speeds covered, stroke count and stroke acceleration magnitudes were assessed. Between-match changes (effect size ±90% confidence interval [CI]) ≥75% likely to exceed the smallest important effect size (ES = .20) were considered practically important. Movement distance (−.63 ± .90, 81% likely) and mean speed (−.61 ± .82, 82% likely) decreased only in match 2. Total strokes played also reduced in match 2 (−11.0 ± 17.7, 84% likely), without changes in stroke acceleration magnitudes. Serve accuracy declined post-match 3 (.76 ± 1.15, 81% likely), though speed did not change. CMJ height was unchanged, though shoulder IR and ER declined (−.57 ± .44, 92% likely), as did agility (.75 ± .35, 99% likely) by post-match 3. CK, pain, fatigue and soreness ratings increased throughout. Same-day tennis matches impair physical capacities and increase fatigue and soreness. Between-match fluctuations in stroke count and movement also infer altered technical elements of match-play.